Bibliographic and citation analysis of publications from a Thai research institute with a defined lifespan: The institute of molecular biology and genetics, 1999 to 2009 - Anchalee Nirachanon (2018)
This study sought to explore the research output of a single research institute in Thailand with a defined life span (1999 to 2009) and to assess the impact of this research through the use of citation analysis. A total of 228 primary research articles met the inclusion criteria (indexed primary research publication) with a combined total of 1696 published pages. Average article length was 7.43 pages. The average impact factor (IF) of the journals in which the papers were published was 2.48 based upon the year of publication. A total of 212 of the 228 papers (93%) had been cited with a cumulative 2376 citations giving an average citation rate of 10.42 citations per paper. This study provides the first detailed assessment of research productivity and impact of the work of a Thai Research Institute and may have value in benchmarking research in institutes in other developing countries. © 2011 Academic Journals.